Pelatihan Penggunaan NST (Nijmeegse Schoolbekwan Test) Pada Guru PAUD - Seila Rizkina; Armanila; Hasnah Siahaan; Idzni Azhima; Reny Khaerany Nisfiary; Mesran; Fatimah (CV. Multi Kreasi Media, 2024)
To notice that children are ready for elementary school is one of the most important things for children that teachers and parents need to care about., But many teachers still don't understand the importance of it the child's readiness embraces the readiness to learn, physical readiness, social skills, Emotional maturity, The ability to think and communicate. Nijmeegse Schoolbekwan Test is a measuring tool that is able to measure students' readiness to enter school. The methods used are lectures and direct practice by teachers. As a result of this community service, the teacher demonstrated the ability to use the NST measuring instrument and was able to interpret the test instrument well, so that the NST was used to measure student readiness in the current year.